- 1-214-256-5804
- info@tutorpace.com

If an expression 3x + 6 + 9 – x is there, we can write this as 2x + 15. This kind of transformation is called simplification of algebraic expressions. To simplify an expression, we need to write the equal degree terms at one place. Then we can add or subtract or simplify those terms. We know Radical expression of both variables and numbers inside a way.

We can write this as individually

= Square root of [(13^2) (x^4) ^2 (z^3) ^2

Here, we can cancel the square and square root

= 13 x^4 z^3

So, the final solution of the given expression is = 13 x^4 z^3.

We can let f (x) = 6x^3 – 5 x^2 + 7x + 100

Now we can plug the value – 3 in the place of x, then we have

f (- 3) = 6(-3)^3 – 5 (-3)^2 + 7(-3) +100

= 6 (- 27) – 5 (9) – 21 +100

= - 162 – 45 – 21 + 100

= - 128